2000
DOI: 10.1017/s0714980800014641
|View full text |Cite
|
Sign up to set email alerts
|

Self-Care Among Older Adults

Abstract: RÉSUMÉCette synthèse de la documentation sur les soins personnels chez les personnes ^gées définit le concept en termes des comportements préventifs et des réponses à la maladie adoptés par les profanes à leur propre bénéfice. Après avoir placé les soins personnels dans leur contexte historique, l'auteur examine les perspectives théoriques et les principales constatations sur son incidence ainsi que les corrélats et les barrières. Cet examen est suivi d'une revue du processus et des résultats des interventions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 110 publications
(117 reference statements)
2
10
1
Order By: Relevance
“…It is likely that a higher education can lead to a better understanding of the importance of performing selfcare directed to improve health as well as easier access to information and resources (45). In terms of gender, no differences were found in our study between female and male older adults, as in Dam asio and Koller's study (2013); however, other studies showed that older women are more oriented to perform self-care (2). Further research is required to verify the presence of gender differences in self-care ability.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…It is likely that a higher education can lead to a better understanding of the importance of performing selfcare directed to improve health as well as easier access to information and resources (45). In terms of gender, no differences were found in our study between female and male older adults, as in Dam asio and Koller's study (2013); however, other studies showed that older women are more oriented to perform self-care (2). Further research is required to verify the presence of gender differences in self-care ability.…”
Section: Discussioncontrasting
confidence: 63%
“…Moreover, positive correlations between levels of education and health self-care behaviours have been identified (9). The influence of gender and living alone on selfcare has not been determined due to contrasting findings of the research (2,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Theorizing in the area of self‐care and decision making has been quite limited (Morrongiello & Gottlieb 2000). Investigators have in general relied on existing, general theories of behavioural change, namely social learning theory (Bandura 1969), the Health Belief Model (Anderson & Newman 1973, Kart & Engler 1995), the Theory of Reasoned Action (Azjen & Fishbein 1980), and the Transtheoretical Model of Health Behaviour Change (Prochaska & Velicer 1997, Prochaska 1998).…”
Section: Introductionmentioning
confidence: 99%
“…A key aspect of health promotion is enabling individuals to control, maintain, and improve their health by making informed decisions (Terris, 1992). As people age and often experience chronic illness, an important aspect of health behaviour is termed self-care (McDonald-Miszczak, Wister, & Gutman, 2001;Morrongiello & Gottlieb, 2000;Ory & DeFriese, 1998). Self-care has been defined as a continuum of caring for the self to enhance health, prevent disease, evaluate symptoms, and restore health, which is organized by perceptions, decisions, and the options available to each individual (Dean & Kickbusch, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Self-care has been defined as a continuum of caring for the self to enhance health, prevent disease, evaluate symptoms, and restore health, which is organized by perceptions, decisions, and the options available to each individual (Dean & Kickbusch, 1995). It therefore encompasses a constellation of preventive health behaviours and responses to illness that influence health, wellness, and illness management and can be particularly beneficial in later life (Morrongiello & Gottlieb, 2000;Wister, 2003). The World Health Organization (1983) added to this definition of self-care the notion that these activities are derived from knowledge and skills originating from both professional and lay experience.…”
Section: Introductionmentioning
confidence: 99%